2014
DOI: 10.12980/apjtb.4.2014c1323
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion fauna and epidemiological aspects of scorpionism in southeastern Iran

Abstract: Based on the results, scorpionism is a serious health problem in this area and increasing knowledge of residents regarding the prevention methods of scorpion stings is recommended. Additional research on the scorpion fauna, their ecological and molecular variety in this part of the country is needed as well as the correlation between scorpions' species and the clinical signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
33
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 9 publications
15
33
1
1
Order By: Relevance
“…Most epidemiological studies have shown that the afflicted body parts are mostly the extremities (hand and foot) [14]. In parallel we found that 85.17% of the investigated patients were stung in their extremities.…”
Section: Discussionsupporting
confidence: 69%
“…Most epidemiological studies have shown that the afflicted body parts are mostly the extremities (hand and foot) [14]. In parallel we found that 85.17% of the investigated patients were stung in their extremities.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, we observed a different distribution of cases between genders in the two studied regions, a finding similar to the reported distribution from Morocco, Iran, and Saudi Arabia [4,[16][17][18][19]. However, according to other studies, in Mexico and Brazil there was no preference in regard to the gender of the affected persons [20].…”
Section: Discussionsupporting
confidence: 87%
“…In Iran, it was previously captured in various weather and climates from tropical regions to snowy highlands by other researchers (Sedaghat et al, 2012). Existence of this species in different countries such as Afghanistan, Armenia, Central Asia, China, Iraq, Turkey, and Oman shows its easy adaptation to various climates (Karataş and Gharkheloo, 2006;Nejati et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…occur annually in the world (Nejati et al, 2014). In Iran, approximately 40 000-50 000 scorpionism cases with about 19 deaths were recorded annually (Kassiri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%